The influence of variable gypsum and water content on the strength and hydration of a belite-calcium sulphoaluminate cement. (19th May 2017) - Beltagui, Hoda; Jen, Gabriel; Whittaker, Mark; Imbabi, Mohammed S.
ABSTRACT: The relative impact and interaction of two components, gypsum and water, in high ye'elimite containing calcium sulphoaluminate-belite cement pastes at an age of 7 days was studied to find the optimum conditions for compressive strength. Using statistical analysis of 149 compressive strength results having a range of water and gypsum contents, the statistical significance of the variables was investigated. X-ray diffraction analysis demonstrated the different hydration processes occurring within samples based on water and gypsum contents, while mercury intrusion porosimetry comparison confirmed the importance of pore structure towards determining ultimate paste strength. Thermodynamic modelling was also used to contribute to the understanding of the microstructural development. The compressive strengths of cement pastes with varying gypsum and water content were shown to be influenced by both factors, with a non-linear dependence on gypsum content observed.